(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2023)
Discharge of industrial effluents and their remediation in relation to crop production are the major concerns. Accordingly, the color, pH, EC, total dissolved solids (TDS), dissolved oxygen (DO), chemical oxygen demand (COD), total hardness, chloride, CO3, HCO3, alkalinity, Cu, Cd, Pb, Mn, Zn, and Cr contents in the effluents discharged from Hazaribagh tannery and Tejgaon textile industries in Dhaka were determined. These effluents had no significant (p≤0.05) effects on soil pH but exerted significant positive effects on the CEC of the soil. The TDS of the effluents were also high but it decreased by alum [K2SO4 Al2 (SO4)3 24 H2O] treatment (0.1%). The DO of the effluents was low and the COD was high leading to a serious threat for aquatic lives. The concentrations of Cd, Pb, Zn, Mn and Cr were high. Filtration through natural sand-gravity-filter acts like Effluent Treatment Plant-ETP and coagulation of effluents by alum decreased the concentrations of Cd and Cr below the permissible limits. The treated effluents were used for the production of vegetables of red amaranth (Amarunthus cruentus), green spinach (Spinacia oleracea) and green amaranth (Amarunthus viridis) grown in a non-polluted soil under pot experiments. Application of treated effluents was found to have significant (p≤0.05) positive effects on the biomass production of the vegetables. The highest amounts of assimilation of Cd in plants were recorded for the Green spinach followed by Green amaranth and for Cr, the order was green spinach followed by red amaranth and green amaranth vegetables grown under the treated effluents of tannery and textile industries. The present study revealed that the natural sand-gravity-filter (i.e., Economic ETP) and alum treatments were found to be effective not only for the remediation of polluted effluents but also improved the growth of vegetables. The use of natural filter and/or alum treatment can be practiced for the remediation of pollution of industrial effluents before discharging from industries. J. Biodivers. Conserv. Bioresour. Manag. 2022, 8(2): 109-118